Bibliometric Analysis on the Development of Capital Structure Research in Manufacturing Firms - Fadila, Ana; Raharja, Surya (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
The manufacturing industry is characterized by its capital-intensive nature and complex production cycles, making capital structure decisions critical for ensuring financial efficiency and business sustainability. This study aims to map the development of literature on capital structure in the manufacturing sector using a bibliometric approach. The analysis was conducted on 226 articles from the Scopus database covering the period from 2000 to 2024, with the aid of the Biblioshiny application on the RStudio platform. The study explores publication trends, institutional affiliations, international collaborations, and thematic structures based on keyword co-occurrence networks. The results indicate a significant increase in publications since 2015, driven by rising global economic uncertainty, technological adoption, and the need for adaptive funding strategies. India and Indonesia emerged as leading contributors, although most publications were domestic in nature and lacked international collaboration. The keyword co-occurrence network revealed two major clusters: internal firm factors such as size and profitability, and external factors including leverage, debt, and macroeconomic risk. The keyword "finance" functions as a bridge between the two clusters, indicating the integration of operational and financial strategies. These findings support the continued relevance of the trade-off theory and the pecking order theory as primary conceptual frameworks.